Social Distancing, Labor Supply, and Income Distribution - Duksang Cho (KDI Journal of Economic Policy, 2021)
The effects of social distancing measures on income distributions and aggregate variables are examined with an off-the-shelf heterogeneousagent incomplete-market model. The model shows that social distancing measures, which limit households' labor supply, can decrease the labor supply of low-income households who hold insufficient assets and need income the most given their borrowing constraints. Social distancing measures can therefore exacerbate income inequality by lowering the incomes of the poor. An equilibrium interest rate can fall when the social distancing shock is expected to be persistent because households save more to prepare for rising consumption volatility given the possibility of binding to the labor supply constraint over time. When the shock is expected to be transitory, in contrast, the interest rate can rise upon the arrival of the shock because constrained households choose to borrow more to smooth consumption given the expectation that the shock will fade away. The model also shows that social distancing shocks, which diminish households' consumption demand, can decrease households' incomes evenly for every income quantile, having a limited impact on income inequality.
Keywords: D31; E21; E43; J20; 330; Covid-19; Income Distribution; Labor Supply; Social Distancing